2017
DOI: 10.3748/wjg.v23.i19.3505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of ulcerative colitis patients who develop acute pancreatitis

Abstract: AIMTo investigate the clinical course of ulcerative colitis (UC) patients who develop acute pancreatitis.METHODSWe analyzed 3307 UC patients from the inflammatory bowel disease registry at Asan Medical Center from June 1989 to May 2015. The clinical course of UC patients who developed acute pancreatitis was compared with that of non-pancreatitis UC patients.RESULTSAmong 51 patients who developed acute pancreatitis, 13 (0.40%) had autoimmune, 10 (0.30%) had aminosalicylate-induced, and 13 (1.73%) had thiopurine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
4
23
1
Order By: Relevance
“…A low need for escalation therapy was documented over the years, and the colectomy rate was quite low at 4.4% (2 patients) over a mean follow-up time of 55 months from the diagnosis of UC. This frequency was similar to a Korean study (7.3%) with a follow-up of 48 months [ 18 ] but different from French data, which reported a higher rate of colectomy (22%) over a long follow-up (68 months). [ 13 ]…”
Section: Discussionsupporting
confidence: 83%
“…A low need for escalation therapy was documented over the years, and the colectomy rate was quite low at 4.4% (2 patients) over a mean follow-up time of 55 months from the diagnosis of UC. This frequency was similar to a Korean study (7.3%) with a follow-up of 48 months [ 18 ] but different from French data, which reported a higher rate of colectomy (22%) over a long follow-up (68 months). [ 13 ]…”
Section: Discussionsupporting
confidence: 83%
“…A recent European multicenter study reported that the subtype of AIP in 91 individuals with coexisting AIP and IBD (58 UC and 33 Crohn’s disease) was almost all type 2 AIP (89/91, type 2 AIP; 2/91, type 1 AIP) 28. On the other hand, the frequency of AIP in IBD patients is very low in South Korea and Japan; 0.4% each, respectively 17,29. Considering the low prevalence of type 2 AIP with IBD, it may be necessary to narrow down candidate IBD patients for diagnosing type 2 AIP.…”
Section: Discussionmentioning
confidence: 99%
“…In the comparison of magnetic resonance cholangiopancreatography (MRCP) findings, MPD stricture was categorized according to extent and multiplicity as follows: MPD narrowing, when the stricture involved any portion of the MPD regardless of the length; and multifocal type, when the stricture involved ≥ 2 sites with intervening normal-looking MPD 17. Common bile duct (CBD) narrowing was also compared between patients with type 2 AIP and ordinary acute interstitial edematous pancreatitis 5.…”
Section: Methodsmentioning
confidence: 99%
“…While the prevalence of IBD in different types of pancreatitis 11–13 and the influence of AIP on the natural disease course of IBD 14 have been described before, whether the presence of IBD influences the natural history of AIP type 2 remains unknown. The present study aims to examine the relationship between AIP type 2 and IBD in patients from two European tertiary care centers and to summarize the existing data in the literature on this topic.…”
Section: Introductionmentioning
confidence: 97%